Prospects of International Cooperation in Training of Specialists in the Field of Art and Culture - E. V. Savelova (Высшее образование в России)
The article presents the experience of the international activities of Khabarovsk State Institute of Culture and partner universities of the People’s Republic of China in the training of specialists for the sphere of culture and art. The purpose of the article is to identify the reasons for increasing China’s interest in cooperation with Russia in the field of higher education, especially artistic and creative, to analyze the problems and prospects of international cooperation in the field of choreographic and musical art. The author presents the practical experience of teaching Chinese students, the effectiveness of which is confirmed by the annual increase in the number of Chinese students and is recognized by the partner universities from China and Chinese students. The author comes to a conclusion that the effectiveness of training of foreign students is greatly influenced by the formation of a multicultural educational environment, the development of bilingual teaching materials, the involvement of students in the creative and scientific life of the Institute.